Representasi “Alpha Female” di Dalam Konten Video “Kick Andy - Gita Savitri dan Paul Mantap Memilih Childfree atau Hidup Tidak Punya Anak” - Rizky Kurniadi; Delvie Nellaety; Syarifah Parameswara Basuki (Dinasti Research, 2024)
This study attempts to describe and analyze the representation of Alpha Female in a feminist perspective. Alpha Female is described as a strong, independent, and confident woman, who puts herself in a dominant position and dares to take initiative in her life. However, the representation of Alpha Female in the media often creates debate among feminist activists as well as the public.. This study discusses and observes the concept of alpha female representation in a feminist perspective in a YouTube video titled